Solomon Islands Health Financing System Assessment : Spend Better - World Bank (World Bank, Washington, DC, 2018)
This report identifies critical opportunities and constraints faced by Solomon Islands health system as it makes progress towards Universal Health Coverage. Protecting the achievements that have been made over recent years, while continuing to improve a broader range of health outcomes, requires effective management of changes in financial and other institutional arrangements in the health sector. Solomon Islands has made some impressive gains in health outcomes over the last two decades. Continued improvements will require more effective governance to manage finite resources at all health service levels. Now more than ever, with decreasing real per capita health expenditure, greater focus is needed on spending health dollars better. More efficiency. More quality of service delivery. More targeted interventions for vulnerable groups to improve equity.